Efficacy and Safety for the Combination of Alpha Lipoic Acid, Gingko Biloba, Vitamin C, Zinc, Magnesium, Vitamin B6, Methylcobalamin, Vitamin E and Chromium Picolinate in the Patients of Sudden Sensorineural Hearing Loss and High Intensity Noise and Vibration Induced Hearing Loss: Post Marketing Surveillance Study - Kiran, Dr. Mayuresh; Pawaskar, Mr. Lalit; Waghambare, Ms. Pramita; Sheikh, Ms. Shaheen (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Sudden sensorineural hearing loss (SSNHL) is defined as sensorineural hearing loss of 30 dB or more over 3 contiguous audiometric frequencies occurring over 72hrs. Conventionally the SSNHL is treated by corticosteroids but it is considered that, addition of antioxidants to the treatment can increase the percentage of patients with the complete recovery. So, this study was conducted to test the efficacy and safety for the combination of Alpha lipoic acid, Gingko biloba, Vitamin C, Zinc, Magnesium, Vitamin B6, Methylcobalamin, Vitamin E and Chromium Picolinate for the treatment of SSNHL and high Intensity noise and vibration induced hearing loss as a concomitant therapy in addition to the standard medical management. Methodology: Out of total 225 enrolled, 208 patients completed the study. Efficacy and safety evaluation was done on day 7 and 14 considering the baseline visit at day 0. Efficacy assessment was done by hearing Impairment questionnaire and hearing related quality of Life. Results: Mean score obtained from hearing impairment questionnaire at day 0 was 19.59 which was reduced to 12.56 at day 7 and was further reduced to 7.70 at day 14. On Visit 1 the mean hearing related quality of life score was 5.24 which was increased to 6.4 at day 7 and was found to be further increased to 7.41 at day 14. Conclusion: The investigational product was efficacious and safe for the treatment of SSNHL and high Intensity noise and vibration induced hearing loss when given as a concomitant therapy to the standard medical management.